2017
DOI: 10.7150/ijms.19933
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of estrogen-deficiency-induced obesity by Ocimum gratissimum

Abstract: Objectives: Menopausal transition in women initiates with declining estrogen levels and is followed by significant changes in their physiological characteristics. These changes often lead to medical conditions, such as obesity, which is correlated with chronic low-grade/subclinical inflammation. Ocimum gratissimum L. is a food spice or traditional herb in many countries; the plant is rich in antioxidants, which possess anti-inflammation activities and multitude of other therapeutic functions.Methods: In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Ocimum gratissimum is a commonly used herbal ingredient in traditional Chinese medicine and is widely distributed in tropical and warm temperate geo-locations. O. gratissimum aqueous extracts (OGE) with its many antioxidant components, has the potential to protect body organs from free radical damage and oxidative stress [10][11][12][13][14][15][16][17][18][19], and possesses many therapeutic functions, including anti-inflammation [20], analgesic and spasmolytic activities [21], antidiarrheal [22], antiviral [23] and anti-hyperglycemic activities [24,25], and improves phagocytic function without affecting the humoral or cellmediated immune system [26]. In anti-cancer activity, the data have found that OGE can induce cell apoptosis in human lung adenocarcinoma A549 cells [27] and human osteosarcoma U2-OS and HOS cells [28].…”
Section: Introductionmentioning
confidence: 99%
“…Ocimum gratissimum is a commonly used herbal ingredient in traditional Chinese medicine and is widely distributed in tropical and warm temperate geo-locations. O. gratissimum aqueous extracts (OGE) with its many antioxidant components, has the potential to protect body organs from free radical damage and oxidative stress [10][11][12][13][14][15][16][17][18][19], and possesses many therapeutic functions, including anti-inflammation [20], analgesic and spasmolytic activities [21], antidiarrheal [22], antiviral [23] and anti-hyperglycemic activities [24,25], and improves phagocytic function without affecting the humoral or cellmediated immune system [26]. In anti-cancer activity, the data have found that OGE can induce cell apoptosis in human lung adenocarcinoma A549 cells [27] and human osteosarcoma U2-OS and HOS cells [28].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence has shown that the gut microbiota can affect estrogen metabolism levels . The decline in estrogen is a serious threat to physiological activities and correlates with endocrine diseases such as type 2 diabetes and obesity , which have a strong correlation with metabolism. Moreover, the gut microbiome has been reported to be associated with many autoimmune diseases, including rheumatoid arthritis and ankylosing spondylitis , which are caused by an abnormal immune response to a patient’s own body.…”
mentioning
confidence: 99%
“…Research on protection against free radical damage has often introduced plant-based antioxidants that can scavenge free radicals, inhibit harmful cellular responses (e.g., inflammation), and stimulate other beneficial cellular responses, which increase cell survival. OGE is one such antioxidant sources that have been widely studied due to its function against oxidative stress 28 - 37 . In this study, FSCS and MTT assay both showed that OGE restored subG1 and G0/G1phase cell count, even if S and G2 phase were not affected.…”
Section: Discussionmentioning
confidence: 99%
“…OGE also modulates the immune response [20] and possess anticancer [21][22][23][24][25][26] and antibacterial activities [27]. OGE, with its many antioxidant components, can also protect body organs from free radical damage and oxidative stress [28][29][30][31][32][33][34][35][36][37]. We speculated that OGE can prevent UVC damage, and that this property can be applied to wound care.…”
Section: Ivyspringmentioning
confidence: 99%
See 1 more Smart Citation